Internal geography and external trade: regional disparities in Italy, 1861-2011 - A'Hearn, B (University of Oxford, 2011)
This paper explores the interactions between external trade and regional disparities in the Italian economy since unification. It argues that the advantage of the North was initially based on natural advantage (in particular the endowment of water, intensive in silk production). From 1880 onwards the share of exports in GDP stagnated and then declined; domestic market access therefore became a key determinant of industrial location, inducing fast growing new sectors (especially engineering) to locate in regions with a large domestic market, i.e. in the North. From 1945 onwards trade growth and European integration meant that foreign market access was the decisive factor; the North had the advantage of proximity to these markets.